Postulate a pluralistic perspective in the training of French teachers in the Democratic Republic of Congo (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
In this text, it is intended to briefly introduce a French teacher training program implemented and tested in Kinshasa (DR Congo). This training promotes a pluralistic perspective, which is based on the diversity and plurality of francophone experiences. Thus, this approach proposes to invest the sociolinguistic, reflexive (and experiential) and historical dimensions in the training of French teachers in this country, so as to help them to emancipate from the pressure and obligation to « fit the standard » of « good French ». This training program is tested with a group of 20 French language teachers from the city-province of Kinshasa. The sociolinguistic research from which this program is derived is also part of a qualitative and hermeneutic approach, with an essential place for the experiences of individuals and the historicity of the researcher.
Keywords: Representations; variation; plural francophonies; French teacher training; D.R. Congo; FLT/SLT; sociolinguistics